EVALUATING THE DISCIPLINARY SANCTIONS GIVEN BY SPORTS CLUBS - (:unkn) unknown (ISTANBUL UNIV, FAC LAW, 2016)
Competition is the essance of sports. Competing needs to success, and success needs discipline. Thus, to provide success, sports clubs have to provide discipline in their own right For that purpose, clubs make some disciplinary regulations for athletes and other staff like trainers, maesseaurs and so on. In this article we tried to study what are the disciplinary sanctions, their classification and legal remedies against them. As a conclusion, if there's a legal regulation and procedure, clubs shall apply these regulations in like manner to regular employers. Otherwise, as a legal remedy, there is different ways, state court or sports federations legal authodes depending on applicant's occupation.
Keywords: Sports law; sports clubs; disciplinary sanctions; athlete; trainer